Cellulose-Based Biosensing Platforms - Morales-Narváez, Eden; de la Escosura-Muñiz, Alfredo; Golmohammadi, Hamed; Zor, Erhan (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
Cellulose empowers measurement science and technology with a simple, low-cost, and highly transformative analytical platform. This book helps the reader to understand and build an overview of the state of the art in cellulose-based (bio)sensing, particularly in terms of the design, fabrication, and advantageous analytical performance. In addition, wearable, clinical, and environmental applications of cellulose-based (bio)sensors are reported, where novel (nano)materials, architectures, signal enhancement strategies, as well as real-time connectivity and portability play a critical role.